EXAMINING THE AWARENESS OF HALAL LOGO AND THE CONFIDENCE LEVEL OF MALAYSIAN FOR THAILAND HALAL PRODUCTS - Jamal Abdul Nassir, Shaari; Muhammad, Khalique; Mohd Khairul Hisyam, Hassan (Allied Business Academics, 2021)
Halal industry has a significant contribution to the global food market. Halal consciousness and mindfulness are sharpened in multi-ethnicities, multi-religious and multilinguistic societies, where Muslim and Non-Muslim coexist. In Malaysia, the constant flow of people as a tourist, commodities, and information from the rest of the world, the interaction zone between Muslim and Non-Muslim has been widening. The main intention of this study was to examine the factors that influence the confidence level of Malaysian customers accepting Thailand halal logo products. To achieve the objective of this study, 500 individuals from the northern part of Malaysia that is Alor Setar, the capital city for the State of Kedah were picked through purposive sampling technique. Data were gathered through a structured survey form. Smart PLS was used to examine the proposed research hypotheses. Results reported marketing and awareness were supported while Thailand's halal logo and devoutness were not supported. This study will be useful for policymakers and future researchers to explore this area in detail.